Urban futures planning for city foresight and city visions - Dixon, Timothy J. 1958-; Tewdwr-Jones, Mark 1968- (Policy Press, 2021)
City visions represent shared, and often desirable, expectations about our urban futures. This book explores the history and evolution of city visions, placing them in the wider context of art, culture, science, foresight and urban theory